2022
DOI: 10.1007/s40257-022-00721-z
|View full text |Cite
|
Sign up to set email alerts
|

New Onset and Exacerbations of Psoriasis Following COVID-19 Vaccines: A Systematic Review

Abstract: Background Vaccination has been promoted to control viral transmission in response to the coronavirus disease 2019 (COVID-19) pandemic. Cases of new-onset or exacerbation of psoriasis, an immune-mediated inflammatory disease, were reported following COVID-19 vaccination. However, a comprehensive review examining the association between COVID-19 vaccination and the occurrence or exacerbation of psoriasis has yet to be performed. Objective The aim of this systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 85 publications
2
32
0
Order By: Relevance
“…Similar timing has also been observed in the occurrence of other autoimmune skin diseases following COVID‐19 vaccination. Wu et al 39 conducted a systematic review and reported that the majority of patients with new‐onset psoriasis presented 1 to 2 weeks (range, 2–21 days) following vaccination. Ganjei et al 40 reviewed 19 cases of alopecia areata occurrence after COVID‐19 vaccination, and 11 cases had a reported onset within 2 weeks (range, a few days to 4 months).…”
Section: Discussionmentioning
confidence: 99%
“…Similar timing has also been observed in the occurrence of other autoimmune skin diseases following COVID‐19 vaccination. Wu et al 39 conducted a systematic review and reported that the majority of patients with new‐onset psoriasis presented 1 to 2 weeks (range, 2–21 days) following vaccination. Ganjei et al 40 reviewed 19 cases of alopecia areata occurrence after COVID‐19 vaccination, and 11 cases had a reported onset within 2 weeks (range, a few days to 4 months).…”
Section: Discussionmentioning
confidence: 99%
“…In the pandemic group, the relative stability of the absolute number of patients with keratinolytic carcinoma and the smaller number of total hospitalized patients with skin disease contribute to the higher proportion of this disease. With regard to psoriasis, one possible reason for the higher proportion of this skin condition in the pandemic group is that most people in China have been vaccinated against COVID‐19, which can lead to new onset and aggravation of psoriasis 13,14 . The reasons for the increased proportion of dermatitis in the pandemic group could be twofold.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is not common trigger for psoriasis symptoms exacerbation ( 59 ), but there are some reports of psoriasis symptoms worsening after vaccination for influenza, pneumococcal pneumonia, and yellow fever ( 60 ). New onset and exacerbation of psoriasis were reported in the systemic review and case series documenting new diagnosis of psoriasis or psoriasis exacerbation after at least one dose of any COVID-19 vaccine ( 61 , 62 ). However, COVID-19 vaccination in Lithuania has actively started in Jan 2021 and lasted until the end of this study (Apr 2021) with 24.7% of Lithuanian population receiving the first dose of the vaccine.…”
Section: Discussionmentioning
confidence: 99%